Dynamics and sources of last glacial aeolian deposition in southwest France derived from dune patterns, grain-size gradients and geochemistry, and reconstruction of efficient wind directions. (15th August 2017) - Sitzia, Luca; Bertran, Pascal; Sima, Adriana; Chery, Philippe; Queffelec, Alain; Rousseau, Denis-Didier
Abstract: Dune pattern, grain-size gradients and geochemistry were used to investigate the sources and dynamics of aeolian deposition during the last glacial in southwest France. The coversands form widespread fields of low-amplitude ridges (zibars), whereas Younger Dryas parabolic dunes mainly concentrate in corridors and along rivers. Spatial modelling of grain-size gradients combined with geochemical analysis points to a genetic relationship between coversands and loess, the latter resulting primarily from dust produced by aeolian abrasion of the coversands. The alluvium of the Garonne river provided also significant amounts of dust at a more local scale. The geochemical composition of loess shows much lower scattering than that of coversands, due to stronger homogenisation during transport in the atmosphere. Overall, sandy loess and loess deposits decrease in thickness away from the coversands. Dune orientation and grain-size gradients suggest that the efficient winds blew respectively from the W to the NW during the glacial, and the W-SW during the Younger Dryas. A comparison between the wind directions derived from the proxy data and those provided by palaeoclimatic simulations suggests a change of the main transport season. Ground surface conditions and their evolution throughout the year, i.e. the length of the season with snow and frozen or moist topsoil, and the seasonal distribution of wind speeds able to cause deflation are thought to have been the main factors that controlled the transport season in the study area. Highlights: We reconstruct sources and dynamics of Last glacial aeolian deposits in SW France. We study dune patterns, grain-size gradients and geochemistry. Geochemistry indicate that loess derived mainly from coversand abrasion. We compare wind directions derived from field proxies with paleoclimate simulations. The variations of wind direction are related to changes in the deflation season.